Laparoscopic treatment of Cushing’s syndrome in a woman in late pregnancy – a case presentation - Sadegh Toutounchi; Anna Makowska; Ewa Krajewska; Patryk Fiszer; Witold Cieśla; Ryszard Pogorzelski; Aleksandra Bartnik; Mirosław Wielgoś; Ewa Bar-Andziak; Maciej Skórski (Videosurgery and Other Miniinvasive Techniques)
Hypercortisolaemia during pregnancy constitutes a serious threat to life of the mother and fetus and may be associatedwith adrenocortical carcinoma. The objective of this study is to present the usefulness of laparoscopic proceduresin treating adrenal tumours in such cases. One 21-year-old woman, 24 weeks pregnant, with hypertension and Cushing’ssyndrome due to a left adrenal tumour, underwent laparoscopic adrenalectomy followed by hydrocortisonereplacement. Spontaneous delivery occurred at the 37/38th week of gestation. At 3 months postpartum the functionof the remaining adrenal gland was found to be normal. Similarly, imaging tests, abdominal CT scan and chest X-rayrevealed no abnormalities. Pregnancy is not a contraindication for performing complicated laparoscopic proceduresunless they are planned in advance and done by an experienced team.